1973
DOI: 10.1017/s0033291700054301
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of luteinizing hormone and of immunoreactive oestrogens (oestradiol) in anorexia nervosa: response to clomiphene citrate

Abstract: SynopsisIn a study of 11 patients with anorexia nervosa, plasma levels of luteinizing hormone (LH) and of oestrogens (oestradiol) were found to be low while the subjects were emaciated. After weight gain, hormone values rose and two patients spontaneously resumed menstruation. Clomiphene citrate was administered on one or more occasions to five patients, and bleeding was induced in the majority of those whose weight exceeded 80% of standard. In two of these patients an irregular cycle resumed for a brief perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
1

Year Published

1974
1974
1993
1993

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 12 publications
3
10
1
Order By: Relevance
“…In patient 2 FSH was undetectable throughout and the small FSH increase seen during the initial study did not occur. In contrast, plasma LH responses were reduced to a lesser degree by estrogen treatment and were not significantly lower on days 4 Effects of pulsatile GnRH injections in anorexia nervosa patients after weight regain Previous studies (16)(17)(18)(19) have shown that LH is secreted in a pulsatile manner, responsiveness to GnRH matures, and plasma estradiol concentrations increase, following weight regain in patients with anorexia nervosa. We therefore administered GnRH to five patients who had regained weight, but who remained amenorrhic, in an effort to determine the effects of increased endogenous estrogen concentrations on gonadotropin responses.…”
Section: Ighdmentioning
confidence: 92%
See 1 more Smart Citation
“…In patient 2 FSH was undetectable throughout and the small FSH increase seen during the initial study did not occur. In contrast, plasma LH responses were reduced to a lesser degree by estrogen treatment and were not significantly lower on days 4 Effects of pulsatile GnRH injections in anorexia nervosa patients after weight regain Previous studies (16)(17)(18)(19) have shown that LH is secreted in a pulsatile manner, responsiveness to GnRH matures, and plasma estradiol concentrations increase, following weight regain in patients with anorexia nervosa. We therefore administered GnRH to five patients who had regained weight, but who remained amenorrhic, in an effort to determine the effects of increased endogenous estrogen concentrations on gonadotropin responses.…”
Section: Ighdmentioning
confidence: 92%
“…The individual hormone concentrations are shown for patient 14 in Fig. 5, and mean data for patients [14][15][16][17][18] are shown in Fig. 6.…”
Section: Ighdmentioning
confidence: 99%
“…In AN the levels of the gonadotropins-the luteinizing (LH) and follicle-stimulating hormone (FSH)-in urine and blood are uniformly low in girls and boys following puberty (Beumont et al, 1972(Beumont et al, , 1973Buvat, Lemaire, Buvat-Herbout, Lepretre, & Fourlinnie, 1983;Brown et al, 1977;Danowski et al, 1973;Emanuel, 1956;Isaacs, Leslie, Gomez, & Bayliss, 1980;Lemaire et al, 1983;Lundberg et al, 1971;Marshall & Fraser, 1971;Russell et al, 1965;Wakeling & DeSouza, 1983;Warren & Vande Wiele, 1973). The reduction in E, levels can be accounted for by depressed resting urinary or serum luteinizing hormone (LH) and follicle-stimulating hormone (FSH) levels (Mecklenburg, Loriaux, Thompson, Anderson, & Lipsett, 1974).…”
Section: Gonadotropin Levelsmentioning
confidence: 99%
“…Amenorrhea is very common; it is clearly not the result of starvation, since it often appears before the onset of inanition (King, 1963;Rahman, et al, 1939;Thoma, 1967). This amenorrhea results from the abnonnally low levels of luteinizing hormone found in anorexics (Beumont et al, 1973(Beumont et al, , 1974 that are apparently due to hypothalamic, and not pituitary, dysfunction, since LH-RH can stimulate a nonnal pituitary release of LH in anorexics (Wiegel mann & Solbach, 1972). Several authors (Landon, Greenwood, Stamp, & Wynn, 1966;Marks, Howorth, & Greenwood, 1965;Neri, Ambrosi, Beck-Peccoz, Travaglini, & Faglia, 1972) have reported abnormally high plasma levels of growth honnone in these patients, although this observation is not substantiated by Danowski, Livstone, Gonzales, Jung, & Khurana (1972).…”
mentioning
confidence: 99%